DAMPAK STRUKTUR MODAL TERHADAP PROFITABILITAS PERUSAHAAN (STUDI KASUS PT SRI REJEKI ISMAN TBK TAHUN 2017-2022) - Hermawan, Muhammad (Brainy: Jurnal Riset Mahasiswa, 2023)
The purpose of this study is to determine the impact of capital structure on company profitability. The method used in this research uses quantitative methods with a descriptive approach, the type of data used in this study is quantitative data. The data source used in this study is secondary data. Secondary data is a source of research data obtained by researchers indirectly through intermediary media obtained. Secondary data is a source of research data obtained by researchers indirectly through intermediary media obtained. The technique of collecting research data is by documentation method. The data sources used in this study are from the Indonesia Stock Exchange (IDX) and annual financial reports. Population is a generalization consisting of objects / subjects that have certain qualities and characteristics that are determined by researchers to be studied and then drawn conclusions. The results of a simple regression analysis test using a partial t test showed a capital structure value of 0.201 which is greater than the predetermined significance therapy of 0.05, then this has no significant relationship or influence on the dependent variable y  profitability, then in this variable H0 is accepted and Ha is rejected.  The cause of no significance or no influence or relationship of capital structure variables on profitability can be caused by other variables not mentioned in this study and various other internal and external factors that have nothing to do with this study.